Moderasi Promosi Penjualan Pada Pengaruh Motivasi Belanja Hedonis Dan Gaya Hidup Belanja Terhadap Impulse Buying Konsumen Shopee - Komang Junita Widhipratiwi; Made Ratih Nurmalasari; Made Mulyadi; Putu Putri Prawitasari (LPPM Politeknik Pratama, 2025)
The rapid development of the current digitalization era has encouraged an increase in e-commerce users in Indonesia. This phenomenon also triggers impulse buying behavior for consumers, especially for Shopee consumers. However, there are inconsistencies in the results of one study related to the influence of hedonic shopping motivation and shopping lifestyle on impulse buying, so further analysis is needed by considering the role of sales promotion as a moderation variable. The purpose of the study was to determine whether hedonic behavior had a significant impact on impulse purchases of shopee consumers in Denpasar. (2) To determine whether the shopping lifestyle has an impact on impulse purchases, especially shopee consumers in Denpasar. (3) To determine whether the promotion of consumer behavior moderates the relationship between hedonistic motivation and impulse purchases of shopee consumers in Denpasar City. (4) To determine whether sales promotion moderates the relationship between impulse purchases and shopping made by shopee consumers in Denpasar. This study uses a quantitative approach method using non-probability sampling techniques. The data analysis techniques used were multiple regression analysis and classical assumption tests. The results and conclusions resulting from this study show that: (1) Hedonic motivation to buy has a positive and significant impact on impulse purchases. (2) A shopping lifestyle that has a positive and significant impact on impulse buying (3) The relationship between impulse buying and hedonic motivation can be strengthened or moderated by sales promotions. (4) Sales promotions can strengthen or moderate the relationship between impulse purchases and shopping habits.